A review of municipal solid waste management in Malaysia - Tarmudi, Zamali; Abdullah, Mohd Lazim; Md. Tap, Abu Osman (Universiti Teknologi Malaysia, 2012)
The tremendous increased of municipal solid waste (MSW) generation in most major cities in Malaysia is observed as a main issue recently. This paper reviews the MSW management comprises many issues arises from the past two decades till the present scenario. It briefly discussed the latest definition of the solid waste based on the Solid Waste and Public Cleaning Management Act (Bill 2007). Out of many MSW discussions, this paper also covers the recent status of the MSW generation, the regulations, the trends of MSW generation as well as local research effort which could a wide interest to the researchers and practitioners. It is hoped that this work will provide a ready reference as additional databases on MSW management situation in Malaysia. Thus an appropriate action can be taken by the relevant authority for their future planning and decision-making purposes.